Một trăm hai mươi mốt 121 timed writings with skillbuilding drills - Clayton, Dean
Are you looking for the ideal tool to perfect your keyboarding skills? With 121 TIMED WRITINGS WITH SKILLBUILDING DRILLS AND MICROPACE PRO 2.0 software you will find the ultimate guide to keyboarding. You can begin this innovative program at any level and it progresses with you as your skills improve. This software will lead you to keyboarding perfection in no time at all!